Perancangan Model Evaluasi Diri Dosen - Agustina Tutik; Synthia Atas Sari; Hartiwi Prabowo (Bina Nusantara University, 2006)
Article present lecturer self evaluation model as complement for IKAD (Lecturer Performance Academic Index). This research used action research analysis and technique of data collecting by library research, discussion by lecturer from any faculty and major, preview the duty and obligation of UBiNus lecturer. Variables and wight for this model are learning (30%), professionalism (20%), research (20%), technology andcomputer (15%), team work (10%), and services to University (5%)